1992
DOI: 10.1093/schbul/18.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Psychobiology in First-episode Schizophrenia at Hillside Hospital

Abstract: Heterogeneity has been a consistent problem in the research and treatment of schizophrenia. Despite marked variation in the onset, phenomenology, treatment response and outcome of schizophrenic patients, our ability to identify subtypes is remarkably limited. A major problem in schizophrenia research has been the use of cross-sectional study designs and heterogeneous patient samples at different stages of the illness and who have been previously exposed to neuroleptics which have potentially confounding effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(74 citation statements)
references
References 92 publications
3
67
0
4
Order By: Relevance
“…There is also no reason to suspect that the sample is not representative of the schizophrenia patient population since similar prevalence rates of intellectual preservation reported by other investigators were observed in this study. Further, total patient mean IQ of approximately 89 in this study is consistent with others, and the sex ratios are also similar to those reported by others Lieberman et al, 1992;Mortensen et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…There is also no reason to suspect that the sample is not representative of the schizophrenia patient population since similar prevalence rates of intellectual preservation reported by other investigators were observed in this study. Further, total patient mean IQ of approximately 89 in this study is consistent with others, and the sex ratios are also similar to those reported by others Lieberman et al, 1992;Mortensen et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Introduction fifth and one-third, will derive little benefit from conventional antipsychotic drug therapy, although a smaller proportion would seem to be completely resistant, [36][37][38] Studies of first episode schizophrenia suggest that, even at an early stage of the illness, a small proportion of patients will show a lack of response, commonly leading to a protracted hospital admission. 38,39 Historically, the concept of non-response to antipsychotic medication was ill defined and largely synonymous with persistent or frequent hospitalisation.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…38,39 Historically, the concept of non-response to antipsychotic medication was ill defined and largely synonymous with persistent or frequent hospitalisation. 37 The use of a criterion threshold reduction in the score on a standardised psychopathology rating scale (such as 20% or 50% reduction on the BPRS total score) has allowed for more reproducible and consistent definitions of poor response to antipsychotic medication.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…However, this attempt has been fraught with both scientific and conceptual difficulties. Epidemiological data have revealed that male gender, 8,39,40 early age of onset of illness, [41][42][43] positive family history of schizophrenia, 44,45 obstetric complications, 46 absence of affective symptoms, 47 severe and lengthy premorbid manifestations, 39,45,48,49 longer duration of untreated psychosis, 50,51 severe negative and cognitive symptoms, 52,53 presence of soft neurological signs, early onset of abnormal involuntary movements, 54 and low level of social functioning 55 were all associated with some degree of treatment refractoriness. However, the reported associations have generally been weak and inconsistent.…”
Section: Mechanisms Of Trsmentioning
confidence: 99%